Development Of Digital Literacy And Environmental Literacy Instruments In Ecology And Biodiversity Materials - Setianingrum, Tri Utami; Sugiharto, Bowo; Sarwanto, Sarwanto (DAS Institute, 2026)
This study aims to develop the feasibility of digital literacy and environmental literacy assessment instruments for junior high school students on ecology and biodiversity material. The research method used is development research with stages of instrument grid compilation, expert validation, and empirical testing. The results of content validation showed an 86.25% feasibility percentage with a highly suitable category. Empirical testing included validity, reliability, and difficulty index tests on 14 essay questions. The validity test results showed 9 valid and 5 invalid questions, while the reliability test yielded a Cronbach's Alpha coefficient of 0.6537, indicating that the instrument's consistency was in the adequate category. Based on these results, it can be concluded that the assessment instrument developed is suitable for measuring students' digital literacy and environmental literacy at secondary school level and is relevant to the demands of 21st-century learning. This instrument is expected to support teachers in the evaluation of continuous science learning and serve as the basis for the systematic and continuous development of contextual literacy assessment in Indonesian junior high schools.